KEARIFAN LOKAL MASYARAKAT BALI DALAM MENCEGAH HIV/AIDS DI KOTA DENPASAR - Ni Luh Gede Hadriani (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
The standard of health in a community can be seen from various indicators, one of these indicators are a case of illness and this is very concerning in lives of people, its called HIV/AIDS. The HIV is very dangerous because since the virus entered the human body, the immune system will weaken because the human immune system has decreased. This makes it easy to get infected with any virus except HIV. Even though various activities have been carried out by the government to suppress HIV/AIDS sufferers, but prevalance HIV/AIDS are still high. One alternative that needs to be implemented is to explore local wisdom such as local wisdom in the form of values, commands and prohibitions, traditional organizations and ceremonies owned by the Balinese people.